Integrasi Tasawuf Dalam Pendidikan Akhlak Dengan Teknik Lagu Qur-Any Karya KH. M. Qoyim Ya’qub - Niswatus Sa’adah, Zaky; Darim , Abu (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article discusses the integration of Sufism in moral education using the Qur'anic song technique developed by KH. M. Qoyim Ya'qub, located at the Al-Urwatul Wutsqo Islamic Boarding School in Jombang. This research is a qualitative study using a case study approach, with data analysis conducted from the time the researcher determined the focus of the study until the research report was compiled. There are three stages in the qualitative research analysis process that occur simultaneously, including data reduction, data presentation, and conclusion drawing, or what can be referred to as verification. The results of this study show that the integration of Sufism in moral education through the Qur'anic song technique by KH. M. Qoyim Ya'qub at the Al-Urwatul Wutsqo Islamic Boarding School in Jombang is carried out systematically and comprehensively. The planning was carried out thoroughly by the caregivers and teachers, including the selection of materials, the formulation of learning objectives, lesson plans, and technical preparations for songs and assessment instruments. The implementation combined demonstrative and contextual approaches through explanations, appreciation of the lyrics' meaning, and singing practice, thereby facilitating the internalization of Sufi values such as patience, gratitude, and humility. This learning has proven to be able to touch the cognitive, affective, and spiritual aspects of students in a balanced manner, and has a significant impact on shaping their character and religious identity.